2016
DOI: 10.1038/nm.4222
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection and lifespan extension by the natural polyamine spermidine

Abstract: 28Aging is associated with an increased risk of cardiovascular disease and death. Here we 29show that oral supplementation of the natural polyamine spermidine extends the lifespan of 30 mice and exerts cardioprotective effects, reducing cardiac hypertrophy and preserving 31 diastolic function in old mice. Spermidine feeding enhanced cardiac autophagy, mitophagy 32 and mitochondrial respiration, and it also improved the mechano-elastical properties of 33 cardiomyocytes in vivo, coinciding with increased titin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

24
807
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 887 publications
(887 citation statements)
references
References 87 publications
24
807
0
7
Order By: Relevance
“…Furthermore, spermidine exhibits anti-inflammatory and antioxidant properties, enhances mitochondrial metabolic function and respiration, promotes chaperone activity and improves proteostasis [4]. Intriguingly, external supplementation of spermidine exerts various beneficial effects on aging and age-related disease in a variety of model organisms, including mice [5,6]. For example, spermidine feeding extends lifespan across species [5,7,8], promotes cardio- [5] and neuroprotection [911], stimulates antineoplastic immune response [12] and may avoid immunosenescence by stimulating memory T-cell formation [13,14].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, spermidine exhibits anti-inflammatory and antioxidant properties, enhances mitochondrial metabolic function and respiration, promotes chaperone activity and improves proteostasis [4]. Intriguingly, external supplementation of spermidine exerts various beneficial effects on aging and age-related disease in a variety of model organisms, including mice [5,6]. For example, spermidine feeding extends lifespan across species [5,7,8], promotes cardio- [5] and neuroprotection [911], stimulates antineoplastic immune response [12] and may avoid immunosenescence by stimulating memory T-cell formation [13,14].…”
mentioning
confidence: 99%
“…Intriguingly, external supplementation of spermidine exerts various beneficial effects on aging and age-related disease in a variety of model organisms, including mice [5,6]. For example, spermidine feeding extends lifespan across species [5,7,8], promotes cardio- [5] and neuroprotection [911], stimulates antineoplastic immune response [12] and may avoid immunosenescence by stimulating memory T-cell formation [13,14]. Many of these anti-aging properties have been causally linked to the capacity of spermidine to ensure proteostasis through the stimulation of cytoprotective macroautophagy [1517].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Oral supplementation of spermidine is capable of extending the lifespan of mice and exerts cardioprotective effects by reducing cardiac hypertrophy and preserving diastolic function in aged mice. These effects are mediated in part by control of autophagic flux 16. Recently, it was demonstrated that spermidine could stimulate autophagy in various tissues including the brain,17 eye18 and heart 19.…”
Section: Introductionmentioning
confidence: 99%